2015
DOI: 10.1074/jbc.m115.656595
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into Specificity of Interactions between Nonconventional Three-finger Weak Toxin from Naja kaouthia (WTX) and Muscarinic Acetylcholine Receptors

Abstract: Background: Cobra's "three-finger" nonconventional toxin WTX allosterically modulates muscarinic receptors (mAChRs). Results: Activity of several WTX mutants was analyzed; toxin spatial structure and dynamics were determined; and complexes of toxin with M1 and M3 mAChRs were modeled. Conclusion: Flexible loop II is the major determinant for toxin binding to different mAChRs. Significance: Structural framework for rationalization of target-specific positive/negative allosteric regulation of mAChRs is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…Potent α-neurotoxicity preceded the evolution of the high-pressure front-fanged system of elapids, as was revealed by our discovery of α-colubritoxin, the first 3FTx isolated and characterized from a non-front-fanged lineage [59]. The toxin was of the same form as had been studied in elapid snakes previously, where they had been called ‘weak neurotoxins’ since they were only weakly potent on mice [137,138,139,140,141,142,143,144,145,146,147,148,149]. A problem that had also confounded studies of Boiga irregularis (brown tree snake), which had thus concluded they were non-venomous based on their effects in a murine model [150,151,152,153,154,155].…”
Section: Resultsmentioning
confidence: 99%
“…Potent α-neurotoxicity preceded the evolution of the high-pressure front-fanged system of elapids, as was revealed by our discovery of α-colubritoxin, the first 3FTx isolated and characterized from a non-front-fanged lineage [59]. The toxin was of the same form as had been studied in elapid snakes previously, where they had been called ‘weak neurotoxins’ since they were only weakly potent on mice [137,138,139,140,141,142,143,144,145,146,147,148,149]. A problem that had also confounded studies of Boiga irregularis (brown tree snake), which had thus concluded they were non-venomous based on their effects in a murine model [150,151,152,153,154,155].…”
Section: Resultsmentioning
confidence: 99%
“…Conformational exchange processes in SLURP-1, Lypd6, and Lypd6b could be due to cis-trans isomerization of the Xxx-Pro peptide bonds, while in Lynx2 and SLURP-2 the exchange processes can be related to the weak protein oligomerization in solution. Interestingly, wild type WTX demonstrates conformation heterogeneity in solution due to cis-trans isomerization of the Arg32-Pro33 peptide bond located in the loop II; and this dynamic process, similarly to the situation with SLURP-1, influences the loop I conformation [ 43 , 65 ]. WTX-P33A mutant lacks the corresponding Pro residue and, therefore, adopts only one isomeric state in solution.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the positively charged residues located at the tip of loop II of toxin WTX, which recognizes the various mAChRs subtypes with low micromolar affinity and limited specificity, were found to be crucial for these interactions (Lyukmanova et al . ).…”
Section: Fts Affecting the Cholinergic Systemmentioning
confidence: 97%